Visibilities in the deaf context within the Pedagogical Residence Program (Research, Society and Development, 2020)
In this article we will discuss the experience of the scholarship holders (residents) of the Pedagogical Residency Program (RP), held in the of a municipal school in the state of Rio Grande do Norte, during the night. of regular classes, serving two Deaf 8th grade students. Therefore, we present as general objective of the article: To analyze about the teaching practices in the scope of the referred program from the experience as residents of the same. The methodology used, critical-dialectical approach, comprises an analysis through theoretical and bibliographical research on studies already conducted, punctuating the trends of research that address the Specialized Educational Care (AEE), thus obtaining the understanding of the teaching and learning process of Portuguese and the construction of this knowledge by the deaf student. Finally, we show as results that the teaching of the Portuguese language for the deaf student, must be permeated by actions "heterrelated" without the intention of "multiculturalize", abandoning the "homodidactic".